Comparing saliva and nasopharyngeal swab specimens in the detection of COVID-19: A systematic review and meta-analysis - Kaveh Nasiri; Aleksandra Dimitrova (Elsevier, 2021)
Background/purpose: Due to the easy transmission of COVID-19, the virus is a threat to global health. Early diagnosis of suspected patients will play an essential role in preventing further spread of COVID-19. The aim of this review study was to evaluate saliva specimen in comparison to nasopharyngeal swab (NPS) specimen in studies selected from various databases. Materials and methods: To achieve the objective of this study, a systematic literature search was carried out in four databases, namely PubMed, Google Scholar, Cochrane Library, and LILACS. The keywords "COVID-19", "Nasopharyngeal Swab", and "Saliva" were utilized via Boolean operators. Results: 14 articles were included in this review study following the eligibility criteria. Based on data presented in studies used in the meta-analysis, there was no significant difference between both specimen types for detection of COVID-19. Heterogeneity test showed that I2 value was 5.790% (<20%). The effect size (risk ratio) of the 14 studies was 0.951 (<1). Conclusion: With the results revealing no significant difference between the two types of specimen in the diagnosis of COVID-19, the use of saliva specimen is preferable for widespread use because it is easily collected without the need for qualified health workers. However, more in vivo studies are required in order to compare and evaluate saliva and NPS specimens in detecting COVID-19 using various techniques.